Entry barriers and growth: The role of endogenous market structure - Helu Jiang; Yu Zheng; Lijun Zhu (Queen Mary University of London, School of Economics and Finance, 2023)
We use China's growth experience as a laboratory to study how reductions in entry barrier contribute to economic growth by inducing a more competitive market structure. The removal of entry restrictions on private firms in the late 1990s and early 2000s made the Chinese economy more competitive and dynamic, propelling the growth acceleration from the early 1990s to late 2000s. We develop a model of endogenous productivity and market structure with heterogeneous firms and frictional entry and calibrate it to Chinese manufacturing from 2004-7. We show about 25% of the productivity growth in 2004-7 is contributed by the reduction of entry barriers during the reforms in the previous decade. While close to 40% of the gain in growth comes from entry bringing about younger firms with higher growth potential, over 60% of the gain in growth comes from entry enforcing tighter market competition which strengthens all active firms' incentive to grow. We also provide suggestive evidence that this mechanism may be at play in a wider economic context.
Keywords: D22; D43; O11; O30; O47; 330; Entry Barriers; Firm Dynamics; Market Structure; Endogenous Growth